Synaptic Zn2+ and febrile seizure susceptibility. (28th November 2016) - Reid, Christopher A; Hildebrand, Michael S; Mullen, Saul A; Hildebrand, Joanne M; Berkovic, Samuel F; Petrou, Steven
Abstract : Zn 2 +, the second most prevalent trace element in the body, is essential for supporting a wide range of biological functions. While the majority of Zn 2 + in the brain is protein‐bound, a significant proportion of free Zn 2 + is found co‐localized with glutamate in synaptic vesicles and is released in an activity‐dependent manner. Clinical studies have shown Zn 2 + levels are significantly lower in blood and cerebrospinal fluid of children that suffer febrile seizures. Likewise, investigations in multiple animal models demonstrate that low levels of brain Zn 2 + increase seizure susceptibility. Recent work provides human genetic evidence that disruption of brain Zn 2 + homeostasis at the level of the synapse is associated with increased seizure susceptibility. In this review, we have explored the clinical, functional and genetic data supporting the view that low synaptic Zn 2 + increases cellular excitability and febrile seizure susceptibility. Finally, the review focuses on the potential of therapeutic Zn 2 + supplementation for at risk patients.